Expanding the European distribution limits of Bruchidius raddianae. First record in Portugal from Vachellia karroo’s infested seeds (Coleoptera: Bruchidae; Fabales: Fabaceae) - López-Núñez, Francisco A.; Duarte, Liliana Neto; Ramos, Rafael Yus; Marchante, Elizabete; Marchante, Hélia (Fragmenta entomologica, 2020)
Several Australian and African Acacia shrubs and trees have been intentionally introduced into the Mediterranean basin for different purposes, but some species become invasive, such as Vachellia karroo (Hayne) Banfi and Galasso (syn. Acacia karroo) (Fabales: Fabaceae). The seed beetles, belonging to family Bruchidae, have a significant ecological and economic importance, either because they can be plant pests or, on the other hand, be used as biocontrol agents against invasive plant species. Bruchidius raddianae (Anton and Delobel, 2003) (Coleoptera: Bruchidae) is native to tropical and subtropical areas, but it has been recently reported from Cádiz and Málaga (southern Spain, 2007) and in the Lampedusa Island (Italy, 2015) from seeds of pods collected from V. karroo. This paper reports 104 specimens reared from seeds collected from V. karroo in Faro (southern Portugal) from August to October 2019, expanding the B. raddianae’ European distribution limits. This is also the first report of its presence in Portugal and the third in Europe.